Hubungan Pengetahuan tentang Manajemen Laktasi dengan Sikap Ibu dalam Pemberian Asi - Indah Wahyuni; Kurnia Wijayanti; Indra Tri Astuti (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Breast milk is the best nutrition for babies because it contains complete nutrients and antibodies that support immunity and optimal growth and development. However, the rate of exclusive breastfeeding in Indonesia is still low, even though its benefits have been proven to reduce the risk of stunting, obesity, and infectious diseases. Mothers' lack of knowledge about lactation management is one of the inhibiting factors, so educational efforts are needed to improve mothers' attitudes towards breastfeeding and support their babies' health. This study aims to determine the relationship between knowledge about lactation management and mothers' attitudes towards breastfeeding at Dr. H Soewondo Kendal Hospital. This study used a quantitative research design with a descriptive correlation and cross-sectional approach. The number of respondents was 38 mothers selected using purposive sampling. The data collection instruments were questionnaires on knowledge about exclusive breastfeeding (15 items) and attitudes towards breastfeeding (16 items). Data analysis was performed using Spearman's rank correlation test. The results of the study showed that most of the breastfeeding mothers were aged 20-35 years (30 respondents), most of them had a high school/vocational school education (25 respondents or 65.8%), and most of them were housewives (21 respondents or 55.3%). Knowledge about lactation management was mostly adequate among 25 respondents (65.8%), and good among 13 respondents (34.2%). Attitudes toward breastfeeding were mostly adequate and good among 19 respondents (50.0%) each. There was a relationship between knowledge about lactation management and mothers' attitudes towards breastfeeding at Dr. H Soewondo Kendal Hospital with a p-value of 0.000. The Spearman correlation test also showed a relationship strength value (rho value) of 0.721, which means that there is a positive relationship: the better the level of knowledge about lactation management, the better the mothers' attitudes towards breastfeeding. It is recommended that nurses be more active in providing comprehensive and structured education on lactation management, not only limited to basic breastfeeding theory, but also covering practical skills, breastfeeding time management, and techniques for dealing with lactation problems commonly experienced by breastfeeding mothers.